Improved First Pass Spiral Myocardial Perfusion Imaging with Variable Density Trajectories - Salerno, Michael (2012)
PURPOSE: To develop and evaluate variable-density (VD) spiral first-pass perfusion pulse sequences for improved efficiency and off-resonance performance and to demonstrate the utility of an apodizing density compensation function (DCF) to improve SNR and reduce dark-rim artifact caused by cardiac motion and Gibbs Ringing. METHODS: Three variable density spiral trajectories were designed, simulated, and evaluated in 18 normal subjects, and in 8 patients with cardiac pathology on a 1.5T scanner. RESULTS: By utilizing a density compensation function (DCF) which intentionally apodizes the k-space data, the side-lobe amplitude of the theoretical PSF is reduced by 68%, with only a 13% increase in the FWHM of the main-lobe as compared to the same data corrected with a conventional VD DCF, and has an 8% higher resolution than a uniform density spiral with the same number of interleaves and readout duration. Furthermore, this strategy results in a greater than 60% increase in measured SNR as compared to the same VD spiral data corrected with a conventional DCF (p<0.01). Perfusion defects could be clearly visualized with minimal off-resonance and dark-rim artifacts. CONCLUSION: VD spiral pulse sequences using an apodized DCF produce high-quality first-pass perfusion images with minimal dark-rim and off-resonance artifacts, high SNR and CNR and good delineation of resting perfusion abnormalities.